BAYANG – BAYANG TEMBAWANG; RUANG INTERAKSI KULTUR DAN BUDAYA MASYARAKAT HUTAN DI KALIMANTAN BARAT - Maria Iqnasia Veren; Agustinus Sutanto (Jurusan Arsitektur dan Perencanaan, 2021)
WHAT IF in the future, WE can no longer see the forest? which is they said have so many beautiful stories and memories of the past. Through this project